Customer Impulse Buying Behavior in Kathmandu - Shrestha, Sajeeb Kumar (Journal of Nepalese Business Studies, 2018)
This study examines customer impulse buying behavior in Kathmandu for the retail sector. Departmental store located in Kathmandu City were approached and collected data. Judgmental sampling technique was used and data were collected from 250 samples. Descriptive statistics and multiple regression analysis were used to summarize the nature of data and to test the hypotheses. The research confirmed that window display, in-store display and promotional signage had significanct influence on impulse buying of customers. No support was found for floor merchandising.